In vivo kinematical validated knee model for preclinical testing of total knee replacement - Shu, Liming; Yao, Jiang; Yamamoto, Ko; Sato, Takashi; Sugita, Naohiko (Computers in biology and medicine, 2021)
A computational knee model facilitates efficient component design evaluations and preclinical testing under various dynamic loadings. However, the development of a highly mimicked dynamic whole knee model with specified ligament constraints that provides high predictive accuracy with in-vivo experiments remains a challenge. In the present study, a musculoskeletal integrated force-driven explicit finite-element knee model with tibiofemoral and patellofemoral joints constrained with detailed soft tissue was developed. A proportional-integral-derivative controller was concurrently added to the knee model to track the boundary conditions. The actuations of the quadriceps and hamstrings were predicted via a subject-specific musculoskeletal model and matched with electromyography results. Compared to in-vivo fluoroscopic results in a gait cycle, the predicted results of the kinematics of the tibiofemoral joint exhibited an agreement in terms of tendency and magnitude (anterior–posterior translation: RMSE = 1.1 mm, r2 = 0.87; inferior–superior translation: RMSE = 0.83 mm, r2 = 0.84; medial–lateral translation: RMSE = 0.82 mm, r2 = 0.05; flexion–extension rotation: RMSE = 0.23°, r2 = 1; internal-external rotation: RMSE = 1.85°, r2 = 0.65; varus–valgus rotation: RMSE = 1.39°, r2 = 0.08). Contact mechanics, including the contact area, pressure, and stress, were synchronously simulated on the tibiofemoral and patellofemoral joints. The study provides a calibrated knee model and a kinematical validation approach that can be widely used in preclinical testing and knee prosthesis design. •A musculoskeletal integrated force-driven finite element knee model was developed and verified by experiments.•The predicted results of kinematics of the tibiofemoral joint exhibited an agreement with in-vivo fluoroscopic results.•Contact mechanics including the contact area, pressure, and stress can be synchronously simulated by the proposed knee model.